Analisis Sistem Antrian dalam Optimalisasi Layanan pada Jabalmart Kefamenanu - Deoniza Antonia Aprilita Lopez; Oktovianus R. Sikas; Faustianus Luan; Leonardus Frengky Obe (Journal of Mathematics Theory and Applications, 2023)
The number of visitors who come to Jabalmart Kefamenanu causes a long queue in front of the cashier. Queuing discipline applied at Jabalmart Kefamenanu is First In First Out, that is customers who come first will be served first. The form of the queuing model in this study at Jabalmart Kefamenanu is a single-phase multi-chanel, namely two or more service facilities and flows through a sibgle line. The purpose of this research is to optimize service at the cashier at Jabalmart Kefamenanu. As for the results of this study, the average service time at each cashier is quite effective because each cashier has a level of service intensity (. That is cashier I level of service intensity () is 0,63, cashier II level of service intensity () is 0,6 and cashier III level of service intensity () is 0,231, it can be concluded that the optimal level of service at the Jabalmart Kefamenanu cashier is quite effective and has been said to be optimal.